2020
DOI: 10.1016/j.cmi.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of seven rapid IgG/IgM antibody tests and the Euroimmun IgA/IgG ELISA in COVID-19 patients

Abstract: Objectives: To evaluate the diagnostic performance of seven rapid IgG/IgM tests and the Euroimmun IgA/ IgG ELISA for antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in COVID-19 patients. Methods: Specificity was evaluated in 103 samples collected before January 2020. Sensitivity and time to seropositivity was evaluated in 167 samples from 94 patients with COVID-19 confirmed with RT-PCR on nasopharyngeal swab. Results: Specificity (confidence interval) of lateral flow assays (LFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
221
4
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(261 citation statements)
references
References 14 publications
(18 reference statements)
28
221
4
8
Order By: Relevance
“…However, this was not possible here as we were testing sensitivity and specificity in specific time frames. Considering that these borderline samples were collected from RT-PCR-positive patients, borderline results were considered positive, consistent with similar studies ( Van Elslande et al, 2020 , Meyer et al, 2020 ). Interestingly, only one pre-pandemic sample with positive anti-MERS-CoV IgG antibodies was found positive by four ELISA kits ( Table 3 and S3), except Lionex, which demonstrated the highest specificity at 98.6% ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, this was not possible here as we were testing sensitivity and specificity in specific time frames. Considering that these borderline samples were collected from RT-PCR-positive patients, borderline results were considered positive, consistent with similar studies ( Van Elslande et al, 2020 , Meyer et al, 2020 ). Interestingly, only one pre-pandemic sample with positive anti-MERS-CoV IgG antibodies was found positive by four ELISA kits ( Table 3 and S3), except Lionex, which demonstrated the highest specificity at 98.6% ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 79%
“…A microplate reader, Epoch 2 microplate spectrophotometer (Bio-Tek, Italy) was used to read the optical density (OD) in all ELISA reactions. Borderline results were considered positive ( Van Elslande et al, 2020 , Meyer et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LFIA tests could prove useful in the emergency room, ambulatory and outpatient settings rather than simply abandoned for its relatively poor performance. We didn’t pool our analysis based on assays from different companies, but other head-to-head studies had shown a variable accordance between different assays within only a small group of participants 28 , 38 , 46 , 55 . A recent study showed a high accordance between Abbott Architect, DiaSorin Liaison, Ortho VITROS, and Euroimmun among 1200 serum samples 56 .…”
Section: Discussionmentioning
confidence: 99%